Exploring the Problems of Elementary School Teachers after Taking on English as Medium of Instruction in District Sialkot - Abdul Qayyum, Sidra Rizwan, (JELM, 2023)
Aim of the study was to explore the problems faced by teachers teaching Social Studies, Mathematics and Science ensuing to taking on English as medium of instruction (MI) at grade 7 and 8. The research was mixed method in nature. All the teachers teaching Social Studies, Mathematics and Science at grade 7 and 8 of District Sialkot comprised the population of the study. Using stratified random sampling technique, a sample of one thousand five hundred Elementary school teachers was selected. The data were collected through a questionnaire constructed on five point Likert scale comprising 5 closed ended items related to perception of taking on English as (MI) and 2 open ended items related to tentative solutions to the problems. Stratified random sampling technique was used to collect data. The sample of the study comprised 1500 teachers722 male, 778 female, 1208, rural and 292 respondents from urban areas teaching Social Studies, Mathematics and Science in English at grade 7 and 8. Frequency, percentage and independent sample t test were used to analyze the data. The research statistics showed that regardless of gender, teachers were facing problems in teaching Social Studies, Mathematics and Science after the change in (MI) from Urdu to English; the teachers of rural areas were facing more problems as compared to teachers working in urban schools. The research also revealed that change of (MI) from Urdu to English without any prior professional development trainings of teachers adversely affected their performance